Faktor Organisasi yang Mempengaruhi Kepatuhan Pelaporan Insiden Keselamatan Pasien di Rumah Sakit Kabupaten Kudus - Rosiana Kusuma; Chriswardani Suryawati; Daru Lestantiyo (Universitas Malahayati, 2026)
ABSTRACT Patient safety is a system designed to improve security in health services, one of which is through reporting patient safety incidents. According to Milgram, factors that influence compliance come from internal factors (individuals), namely personal responsibility and external factors (organizations), namely location status, legitimacy of authority figures (legitimacy of authority figures), status of authority figures, support from colleagues and proximity of authority figures. To analyze organizational factors in compliance with reporting Patient Safety Incidents (IKP) at Kudus Regency Hospital. This study is a type of qualitative research using an in-depth interview method. The subjects involved in this study were 22 as main informants and 7 as triangulation informants. Data collection in the study was carried out using interview and documentation methods. Analysis of research data was carried out using qualitative descriptive analysis. The research shows that compliance with patient safety incident reporting (IKP) in hospital